2011
DOI: 10.1587/elex.8.1899
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a microstep DFA vulnerability estimation method

Abstract: Abstract:Recently, various studies of attack methods of round reduction differential fault analysis (DFA) using fault injection in block cipher-implemented microcontrollers have been reported. However, few studies have focused on the quantitative evaluation method of round reduction DFA vulnerability using detailed fault injection timing dependency of attack success rate. This is required to improve microcontroller security. Hence, we propose a quantitative evaluation method against round reduction DFA using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…Our results show that the double addition attack succeeded 60 times in 1000 trials. The experimental result was obtained in the same manner with [6]. In this result, we conclude that the round addition by command bypassing is feasible for practical block cipher systems.…”
Section: Experimental Results Of Clefiasupporting
confidence: 64%
See 1 more Smart Citation
“…Our results show that the double addition attack succeeded 60 times in 1000 trials. The experimental result was obtained in the same manner with [6]. In this result, we conclude that the round addition by command bypassing is feasible for practical block cipher systems.…”
Section: Experimental Results Of Clefiasupporting
confidence: 64%
“…On the other hand, Kaminaga et al [6] show the effectiveness of a combination of multiple branches and a brown-out detector (BOD), which is a type of low voltage detector, in their experiment using the ATmega168 (Atmel, USA) microcontroller. According to their experiment, round reduction did not work against the combination of triple branches and BOD.…”
Section: Introductionmentioning
confidence: 99%
“…Differential fault analysis (DFA) using operation bypassing is an effective attack technique for cipher-implemented microcontroller [1]. On the basis of this technique, we have shown that round addition DFA using a bypassing increment or decrement command is effective for attacks against cipher-implemented microcontrollers.…”
Section: Introductionmentioning
confidence: 99%